La C.E.E : un modele juridique pour une plus grande integration economique en Afrique australe. Volume 1-2 - Vrancken, Patrick Henri Ghislain (Department of Public Law, 2023)
The purpose of this thesis is to answer the following question : Ii the E.E.C. in fact a legal model for greater economic integration in Southern Africa? Part One of the thesis provides a description of the organization of the E.E.C After a brief historical introduction, Section One analyses the Community's main institutions : their composition, their function, and their decision-making mechanisms. The different legal instruments of Community law, the relationship between this law and traditional international law on the one hand and the national law of the member states on the other, the interaction between the Council, the Commission and the European Parliament as well as the financing of the organization are also considered in some detail. Section Two examines some of its most important spheres of activity, namely, free movement of goods, free movement of persons, freedom to provide services, free movement of capital, the rules on competition, regional policy, fiscal harmonization and V.A.T., legal equalization processes and transport. A definition of the internal market and an account of other innovations introduced by the Single European Act in the field of the organization's activities concludes this section on the E.E.C Part Two deals with the principal organizations of economic cooperation in Africa, of which South Africa is not a member, and examines to what extent the African continent has been influenced by this European experience. After a short historical account leading to the existence of these African organizations, each kind of institution in these different organizations is dealt with separately in Section One, particular attention being given to their composition, their functions, and their different legal instruments. This is followed by a study of the law of these organizations and to what extent it differs from the traditional international law, as well as the interaction between the different institutions and the financing of these organizations. Section Two examines the main fields of activity of the organizations studied in this Part, namely, the suppression of customs duties, the common customs tariff, the removal of technical barriers to trade, free movement of persons, freedom to provide services, free movement of capital, transport and communication, natural resources, social and cultural matters, regional policies, industrial development, and other fields of activity. Part Three is divided into three chapters. The first one is the study of the principal instruments of multilateral economic cooperation to which South Africa belongs, that is, the Southern African Customs Union, and Monetary Area and the Economic Community of Southern Africa. The second Chapter presents general comparisons between the institutional structure of the organizations, their fields of activity, as well as the supranationalism which they could eventually enjoy. Finally, the third Chapter consists of conclusions which .are of a more personal note, that is to say, a presentation of an original system based on the study made in this thesis, particularly of the E.E.C., a system which, in my opinion, could be applied to the internal law in South Africa and at the same time could offer a model of economic and political integration in Southern Africa.